Correlations between Serum Interleukins-2,-4 Levels and Some Biochemical Parameters in Iraqi Patients with Osteoporosis - Ahmed, Hind Sh. (Journal of the Faculty of Medicine Baghdad, 2017)
Background: Osteoporosis is a frequent disease that is manifested by reduced in mineral density and raised in fracture risk. Recent studies have indicated that osteoporosis is caused by composite connections among local and systemic regulators of bone cell function.Objective: The purpose of this study was to investigate the relationship between interleukin-2, interleukin-4, and some biochemical markers in Iraqi patients with osteoporosis.Patients and Methods: Forty five osteoporotic patients were incorporated in this study (30 women and 15 men). Serum fasting glucose, lipid profile, alkaline phosphatase activity, calcium, magnesium, interleukin-2, and interleukin-4 were measured in osteoporotic patients and compared them with the control group.Results: There was a significant increase in serum fasting glucose, lipid profile except high density lipoprotein cholesterol, and serum alkaline phosphatase activity in osteoporotic patients as compared to the control, (P=0.001). Also, there was a significant increase in interleukin-2 and interleukin-4 in osteoporotic patients as compared to the control, (P= 0.01). While there was a decrease in serum calcium and magnesium levels in osteoporotic patients as compared to the control. Also, there was a significant positive correlation between serum alkaline phosphatase activity with interleukin-2 and interleukin-4 levels in osteoporotic patients, (P= 0.01).Conclusion: Elevated levels of interleukin-2 and interleukin-4 along with some biochemical markers like; serum alkaline phosphatase in osteoporotic patients might include significant functions in the pathogenesis of osteoporosis.